Correction of Cerebrospinal Fluid Protein in Infants With Traumatic Lumbar Punctures. Issue 10 (October 2017) - Lyons, Todd W.; Cruz, Andrea T.; Freedman, Stephen B.; Arms, Joseph L.; Aronson, Paul L.; Fleming, Alesia H.; Kulik, Dina M.; Mahajan, Prashant; Mistry, Rakesh D.; Pruitt, Christopher M.; Thompson, Amy D.; Nigrovic, Lise E.
Abstract : In our multicenter cohort of infants ⩽60 days of age, we identified 2646 infants with a traumatic lumbar puncture, of which 31 (1.2%) had bacterial meningitis. For every 1000 cerebrospinal fluid red blood cells/mm 3, cerebrospinal (cerebrospinal fluid) protein increased 1.1 mg/dL (95% confidence interval: 1.0–1.2 mg/dL).